ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN DANA PERBANKAN SYARIAH DI INDONESIA SEBELUM DAN SESUDAH KEBIJAKAN AKSELERASI PERBANKAN SYARIAH TAHUN 2007/2008 - Khatimah, Husnul (Fakultas Ekonomi Universitas Islam 45, 2009)
This research was aimed to examine about factors related to amount offinancing syariah banking. Complexity effects of non performing financing (NPF), Wadiah certificate of Indonesian Banking (SWBI) and third funding sector (DPK) before and after syariah banking acceleration policy.  This research was carried out at Jakarta with sampling was conducted by purposive sampling technique, by criteria Bank Muamalat Indonesia was oldest syariah bank in Indonesia. Collecting data was conducted by report of Statistical Syariah Banking 2006 - 2008. Data analysis used dual regression linear method. The result of research showed that DPK, NPF AND SWBI rate affect as positive and significant to financing fluctuation of syariah banking. Before syariah banking acceleration policy, financing of syariah banking growth more rapidly if compared with after syariah bankingacceleration policy.